Evidence-based intrapartum care practice and associated factors among obstetric care providers in Jimma Zone public hospitals, southwest Ethiopia: A cross-sectional study - Diriba Wakjira; Eneyew Melkamu Andualem; Azmeraw Bekele; Desalew Tilahun Beyene (SAGE Open Medicine, 2025)
Background: Evidence-based practice in intrapartum care is critical for lowering maternal and neonatal mortality and morbidity. Evidence-based practice, according to the World Health Organization Quality of Care Framework for Maternal and Newborn Health, is an important component of intrapartum care. However, little is understood about evidence-based intrapartum care practice in Ethiopia, particularly in the study setting. Objective: To assess evidence-based intrapartum care practice and associated factors among obstetric care professionals in Jimma Zone public hospitals in Southwest Ethiopia. Methods: A facility-based cross-sectional study was carried out on 217 obstetric care providers in Jimma Zone public hospitals in southwest Ethiopia. The study used a census approach to include all eligible participants within the specified population. Data were collected from June 1 to 30, 2023, using semistructured self-administered questionnaires. The collected data were entered into EpiData version 4.6 and exported to Statistical Packages for Social Sciences version 25 for analysis. Multivariable logistic regression was run to see the association between evidence-based intrapartum care practice and predictor variables. Statistical significance was set at p -values less than 0.05 in the multivariable logistic regression. Results: Overall, 41.2% (95% CI: 40.8–42.3) of obstetric care providers in Jimma Zone public hospitals used evidence-based practices for intrapartum care. Attending in-service training (AOR (95% CI): 3.5 (1.61–9.71)), accessibility of obstetric care guidelines (AOR (95% CI): 2.082 (1.222–3.547)), having regular case presentation (AOR (95% CI): 2.5 (1.234–6.743)), having knowledge (AOR (95% CI): 2.3 (1.222–3.547)), attitude of obstetric care providers (AOR (95% CI): 1.847 (1.065–3.204)), having less than 2 years of work experience (AOR (95% CI): 1.32 (1.012–3.56)), and having 2–5 years of work experience (AOR (95% CI): 3.49 (1.23–6.312)) were among factors significantly associated with evidence-based intra-partum care practice of obstetric care providers in Jimma Zone public hospitals. Conclusions: This study indicated that the majority of obstetric care providers did not practice evidence-based intrapartum care, which requires attention from all stakeholders. It is recommended for hospitals in the Jimma Zone to make guidelines available, provide in-service trainings, and identify systematic strategies to improve the knowledge and attitude of obstetric care providers.